IMPROVING STUDENTS' VOCABULARY MASTERY THROUGH OSTENSIVE MEANS (A CLASSROOM ACTION RESEARCH IN THE FOURTH YEAR OF SDN 1 DONOHUDAN) - MURTIANI , ENY (2007)
Teaching vocabulary to elementary school is to introduce simple English words. The objective of this research is to describe the improvement of vocabulary mastery of the students who learn vocabulary through Ostensive Means, and the strength and weaknesses of teaching vocabulary using Ostensive Means to the students at SDN Donohudan I. In this research, the writer uses action research and takes 49 students as the subject of the study. Technique of the data collection is test, interview, and observation. The data are analyzed using qualitative analysis. The writer can draw conclusions as follows: teaching vocabulary using Ostensive Means is successful, because the students are able to improve their vocabulary mastery especially English. The strength of teaching vocabulary using Ostensive Means are the students can pronounce words correctly and understand the meaning of words. While, the weaknesses of teaching vocabulary using Ostensive Means are the teacher needs more energy and more material to teach the students.